PENGARUH CORPORATE GOVERNANCE, MANAJEMEN LABA DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2013-2015) - atami, Audina gita; Basri, Yesi Mutia Basri Mutia; Kurnia, Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aim of this study are examine the effect of corporate governance, earnings management and capital intensity to tax aggressiveness. The proxy of corporate governances are independent commissioner, audit committee and institutional ownership. Cash effective tax rates (CETR) is used to measure tax aggressiveness. This study uses secondary data with a sample of 62 companies listed on the Stock Exchange during the period 2013-2015. Determination of the sample was made by applying purposive sampling method. The results of this study showed that the variable of institutional ownership and capital intensity have significant effect toward tax aggressiveness. Meanwhile, independent commissioner, audit committee and earnings management have no significant effect toward tax aggressiveness.Keywords :Corporate Governance, Earnings Management, Capital Intensity, Tax Aggressiveness.